Drug treatment options for premature ejaculation. (3rd July 2018) - Waldinger, Marcel D.
ABSTRACT: Introduction : Various drugs are available for lifelong and acquired premature ejaculation (PE), but only dapoxetine and Fortacin TM have been officially registered. On the other hand, all sorts of pharmacologically not-investigated over-the-counter-products (OTCs) are used by men with complaints of PE with normal ejaculation time durations (subjective PE). There is a need to critically review the current state of registered and nonregistered drugs for PE. Areas covered : In this review, the authors use the guideline of the International Society for Sexual Medicine (ISSM) for the treatment of PE and provide evidence-based recommendations for the pharmacotherapy of lifelong and acquired PE. This should always be accompanied by psychoeducation, counseling, and information about common and rare side effects of the various available drugs. Expert opinion : As long as subjective PE is not officially recognized as the third PE subtype, registration authorities will continue to demand drugs for subjective PE to be studied in men with lifelong PE. This is unfortunate as the method and design of studies of drugs for subjective PE differ from those of lifelong PE but also because drugs for subjective PE need to be investigated in men with subjective PE and not in men with lifelong PE.